Highly efficient electroluminescence polymer blend in poly(p-phenylene vinylene) derivatives - Jin, SH; Gal, YS; Cho, HN (TAYLOR & FRANCIS LTD, 2002)
Asymmetric and color tunable polymer blend systems from poly[2-(3'-dimethylalkylsilylphenyl)-1,4-phenylene vinylene] (m-SiPhPPV) and MEH-PPV were characterized. The maximum absorption (UV) and photoluminescence (PL) peaks of the blending system were proportional to the their blending ratios. The electroluminescence (EL) spectra with various blending ratios of the m-SiPhPPV and MEH-PPV were mainly contributed from the MEH-PPV part. The turn-on voltages for single-layer light emitting diodes (LEDs) are about 3V for m-SiPhPPV and MEH-PPV and 8V for blending systems.
Keywords: DIODES